IMPLEMENTASI PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK DALAM PEMBELAJARAN IPA - Khoirul Fikri Firmansyah; An Nuril Maulida Fauziah; Edi Maryanto (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to describe improving cognitive learning outcomes using a model Problem Based Learning (PBL), as well as students' responses to learning in class. This research is classroom action research (PTK). Participants in this research were 29 class VIII junior high school students. The data collection technique used was the test method, and questionnaires were then analyzed quantitatively descriptively. The research results obtained show that the value of students' cognitive learning outcomes has increased quite significantly, where in cycle I and cycle II there has been an increase in learning completeness in terms of test results. pretest and posttest. Results of analysis of student responses to learning problem based learning also shows positive response results from students with very good criteria. Based on the results of this research, it can be concluded that there is an influence of the learning model problem based learning in improving cognitive learning outcomes in terms of learning completeness and positive responses by junior high school students in class VIII.